Research and development of hash retrieval technology based on deep learning - Mingwen YUAN; Jiangbo QIAN; Yihong DONG; Huahui CHEN (Dianxin kexue)
In the era of big data,data shows the characteristics of high dimension,large amount and rapid growth.How to efficiently retrieve similar data from a large amount of complex data is a research hotspot.By mapping data to binary codes,the hashing technique can significantly accelerate the similarity calculation and reduce storage and communication overhead during the retrieval process.In recent years,deep learning has shown excellent performance in extracting data features.Deep learning-based hash retrieval technique has the advantages of high speed and accuracy.The methods and advanced development of deep learning hashing were mainly summarized,and the future of research direction was briefly discussed.